Elements of Neuroanthropology - Lende, Daniel H.; Casper, Breanne I.; Hoyt, Kaleigh B.; Collura, Gino L. (Frontiers in Psychology, 2021)
Neuroanthropology is the integration of neuroscience into anthropology and aims to understand “brains in the wild.” This interdisciplinary field examines patterns of human variation in field settings and provides empirical research that complements work done in clinical and laboratory settings. Neuroanthropology often uses ethnography in combination with theories and methods from cognitive science as a way to capture how culture, mind, and brain interact. This article describes nine elements that outline how to do neuroanthropology research: (1) integrating biology and culture through neuroscience and biocultural anthropology; (2) extending focus of anthropology on what people say and do to include what people process; (3) sizing culture appropriately, from broad patterns of culture to culture in small-scale settings; (4) understanding patterns of cultural variation, in particular how culture produces patterns of shared variation; (5) considering individuals in interaction with culture, with levels of analysis that can go from biology to social structures; (6) focusing on interactive elements that bring together biological and cultural processes; (7) conceptual triangulation, which draws on anthropology, psychology, and neuroscience in conjunction with field, clinic, and laboratory; (8) critical complementarity as a way to integrate the strengths of critical scholarship with interdisciplinary work; and (9) using methodological triangulation as a way to advance interdisciplinary research. These elements are illustrated through three case studies: research on US combat veterans and how they use Brazilian Jiu Jitsu as a way to manage the transition to becoming civilians, work on human-raptor interactions to understand how and why these interactions can prove beneficial for human handlers, and adapting cue reactivity research on addiction to a field-based approach to understand how people interact with cues in naturalistic settings.